Argentinean National Plant Protection Network Website - Gasoni, Amelia Laura (2017)
The Argentinean National Plant Protection Network (RedNPV) was created in 2006 as a proposal of the National Plant Protection Program (PNPV), National Institute of Agricultural Technology (INTA). The National Plant Protection Network (RedNPV) main objective is to articulate national scientific-technological capabilities in Plant Protection.